Impact of Jacobson Relaxation on Dialysis Adequacy in ElderlyHemodialysis Patients - Shirin Madadkar Dehkordi; Mehdi Basiri Moghadam (Golestan University of Medical Sciences, 2017)
Background: Dialysis adequacy is one of the determining factors for survival in elderly patients. Improving the dialysis adequacy highly affects the remission and prognosis of old dialysis patients. Current study was conducted to evaluate the effects of Jacobson relaxation technique on dialysis adequacy in elderly people, who are under dialysis treatment. Methods: ods: This is a clinical trial performed on 80 hemodialysis patients in two hemodialysis centers of Gonabad and Yazd, Iran, in 2013. The patients were selected through purposive sampling method, and randomly assigned into the two groups of control (n=40) and intervention (n=40). The participants in intervention group were provided by three sessions of relaxation training, and were asked to perform the relaxation daily for six weeks, while the control group just received the routine cares. Afterwards, the adequacy of dialysis was compared between the two groups. The data was collected using the demographic information, and the dialysis adequacy was calculated by KT/V equation.  Results: A significant statistical difference was found between groups regarding the mean difference of dialysis adequacy in pre- and post-intervention (P<0.001).Besides, dialysis adequacy increased post-intervention in the case group and decreased slightly in the control group compared to pre-intervention. Conclusion: Training and performing the relaxation method lead to an  improved dialysis adequacy in elderly patients under hemodialysis.